Effects of saddle height on pedal force effectiveness - Bini, R. R.; Hume, P. A.; Crofta, J. L. (Procedia Engineering, 2011)
Bicycle saddle height configuration may affect pedal force application. Our aim was to compare pedal force effectiveness for different saddle height configurations. Eleven cyclists (38 ± 12 years) and eleven triathletes (44 ± 8 years) with competitive experience performed 2-min trials at four different saddle heights (preferred, high, low, theoretical optimal) each separated by one minute of rest. Workload was normalized by body weight and pedaling cadence was visually controlled by the athletes at 90 ± 2 rpm for all trials. The preferred saddle height replicated the horizontal and vertical configuration of each athlete's bicycle. High and low saddle heights were selected to elicit ± 10° knee flexion from knee flexion at preferred saddle height. Guidelines from Peveler were used to set the theoretical optimal saddle height based on 25° knee flexion when the pedal crank was at the 6 o`clock position. Knee joint angles were measured with a goniometer prior to each trial. Normal and shear forces were measured using an instrumented right pedal and pedal-to-crank angle was measured using an angular potentiometer. A reed switch attached to the bicycle frame detected the position of the crank in relation to the pedal revolution. Forces on the pedal surface were resolved into the tangential force on the crank to compute force effectiveness (ratio between tangential and resultant force applied on the pedal). Magnitudes of differences between the saddle heights were assessed by effect sizes (ES) for the average total (resultant) force and force effectiveness. To elicit ± 10° knee flexion, changes of ± 3% of the preferred saddle height were required. Changes in average resultant force with saddle height were trivial (1% for preferred versus optimal; ES = 0.2) to moderate (5% for high versus low; ES = 0.8). Changes in force effectiveness with saddle height were small (2% for preferred versus optimal; ES = 0.3) to moderate (6% for high versus low; ES = 1.0). Lower saddle heights produced higher resultant force but lower force effectiveness. Saddle height changes resulted in moderate effects for pedal resultant force and force effectiveness for most saddle height comparisons.